2023
DOI: 10.1021/acs.jcim.2c01091
|View full text |Cite
|
Sign up to set email alerts
|

Combining Group-Contribution Concept and Graph Neural Networks Toward Interpretable Molecular Property Models

Abstract: Quantitative structure–property relationships (QSPRs) are important tools to facilitate and accelerate the discovery of compounds with desired properties. While many QSPRs have been developed, they are associated with various shortcomings such as a lack of generalizability and modest accuracy. Albeit various machine-learning and deep-learning techniques have been integrated into such models, another shortcoming has emerged in the form of a lack of transparency and interpretability of such models. In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The matrix B 00 N M 00 denotes the interaction terms for N molecules, where each row corresponds to b″ in (9).…”
Section: Methods Ilr Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The matrix B 00 N M 00 denotes the interaction terms for N molecules, where each row corresponds to b″ in (9).…”
Section: Methods Ilr Architecturementioning
confidence: 99%
“…Materials science has greatly benefited from advancements in machine learning (ML) and deep learning (DL) techniques [1][2][3][4][5][6] . These techniques have revolutionized the prediction of molecular properties, leveraging traditional computational approaches, such as the group contribution (GC) method [7][8][9] , quantitative structureactivity/property relationship (QSAR/QSPR) method [10][11][12][13] , quantum mechanics (QM), and molecular dynamics (MD) calculations [14][15][16][17][18][19][20][21][22][23][24][25][26] . Graph neural networks (GNNs) have emerged as a promising DLbased method for property prediction by embedding molecular structures in a graph architecture 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of the evaluation of the enthalpy of formation ∆H f of organic molecules from their molecular structure, the Group Contribution (GC) approach is one of the most important and widely applied methods [1][2][3][4][6][7][8][9][10][11][12][13][14][15]. The original GC method is based on the assumption that a molecule can be decomposed into molecular fragments which are in essence mutually independent, and the molecular property of interest is the sum of the individual properties of the molecular fragments.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of time, a larger number of further studies employing the GC methodology to evaluate the heat of formation of organic molecules have been reported, including the works by Benson and co-workers [2], Joback and Reid [3] and Gani et al [4,5]. Recently, a study relevant in this context and employing neural networks was also reported [6].…”
Section: Introductionmentioning
confidence: 99%